PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PARK HOTEL JAKARTA SKRIPSI - Cendy Bill Clinton; Paryoto (LPPM Universitas Asa Indonesia, 2016)
Purpose- The aim of this research is to find out the effect of motivation and work environment on employees’s performance in Park Hotel Design/methology/approach- The Saturated sample are selected, excluding sample for validity test and reliability one. The descriptive and quantitative methods of analysis were implemente. The Calassic assumption, multiple regression, t-test, F-test and coorelation & determination-test were applied. Findings- The Motivation and Work environment have effected the employees’s performance. However, both variables have effected in low category, while by simultaneous, they are in moderate category. Research limitations- The limitation of variables are the factor in this particular point. Practical implications- The management need to improve both in motivation and work environment